2021
DOI: 10.1111/bjc.12343
|View full text |Cite
|
Sign up to set email alerts
|

Is alcohol use associated with psychological treatment attendance and clinical outcomes?

Abstract: Objectives To investigate associations between alcohol use, psychological treatment attendance, and clinical outcomes. Methods We analysed electronic health records for N = 7,986 patients accessing psychological treatment for common mental disorders. Data were collected for pre‐treatment alcohol use (average units per week) and severity of dependence (SDS), number of therapy contacts attended, pre‐ and post‐treatment anxiety (GAD‐7), and depression (PHQ‐9) symptom severity. Hierarchical regression was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Consistently across all measures, patients with hazardous alcohol use at baseline showed the most improvements. Based on these results, we can conclude that patients with hazardous alcohol use achieve at least as good a therapeutic outcome on the symptom assessment instruments as patients without hazardous use, as shown in other studies ( Hunt and Delgadillo, 2022 ). This means that therapists, clinicians, and healthcare facilities need not hesitate to treat patients with hazardous alcohol use for anxiety and depression problems under the assumption that their alcohol consumption makes it difficult to benefit from psychologicaltreatment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistently across all measures, patients with hazardous alcohol use at baseline showed the most improvements. Based on these results, we can conclude that patients with hazardous alcohol use achieve at least as good a therapeutic outcome on the symptom assessment instruments as patients without hazardous use, as shown in other studies ( Hunt and Delgadillo, 2022 ). This means that therapists, clinicians, and healthcare facilities need not hesitate to treat patients with hazardous alcohol use for anxiety and depression problems under the assumption that their alcohol consumption makes it difficult to benefit from psychologicaltreatment.…”
Section: Discussionsupporting
confidence: 82%
“…At follow-up, there was also no significant difference between the groups. Patients with hazardous alcohol use seem as likely to complete psychological treatment as other patients ( Hunt and Delgadillo, 2022 ) and they also seem to be at least as likely to answer questionnaires at completion and follow-up as other patients.…”
Section: Discussionmentioning
confidence: 99%
“…We did find that self-identifying as having an alcohol problem, the number of days drinking (in the month prior to entry into prison) and dependance were all indicative of better engagement with the Engager intervention. Research has suggested that alcohol users are just as likely to engage in and benefit from psychological therapy, in fact those with moderate alcohol use may gain more from therapy [19]. This may explain the increased attendance for this group in the Engager intervention, why we also saw that participants attending more sessions were receiving more therapeutic sessions and that we have defined this group as "crisis but coping".…”
Section: Discussionmentioning
confidence: 78%
“…This may explain the increased attendance for this group in the Engager intervention, why we also saw that participants attending more sessions were receiving more therapeutic sessions and that we have defined this group as "crisis but coping". It is postulated that moderate levels of alcohol use are linked to a capacity to tolerate distress and so these participants were able to tolerate more anxiety provoking situations and not rely on safety and avoidant behaviors [19], thus possibly explaining engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation